Islamic Republic of Iran : Cost Assessment of Environmental Degradation - World Bank (World Bank, Washington, DC, 2020)
The objective of this report is to provide an estimate of the cost of environmental degradation in Iran. Despite the difficulties involved in assigning monetary values to environmental degradation, such estimates can be a powerful tool to raise awareness about environmental issues and facilitate progress toward sustainable development. It is hoped that this study will provide an instrument for policymakers to better integrate the environment into economic development decisions. In 2002, the annual cost of environmental degradation in Iran was estimated at 4.8 to 10 percent of GDP, with a mean estimate of 7.4 percent (equivalent to US$8.4 billion or IRR 67,300 billion).